Proposed new interior design scheme of society of The Blind Centre for Society of the blind in Malaysia (Perak Branch) at Jalan Medan Ipoh 4, Taman Ipoh Timur, 31400 Ipoh, Perak / Sadiah Ismail - Ismail, Sadiah (Faculty of Architecture, Planning and Surveying, 2011)
The final project for Diploma in Interior Architecture student is a manifestation towards the student’s knowledge about the whole aspect on Interior Architecture that had been learnt from basic to the final presentation on the proposal of design. The project that had been chosen for the final project is to proposed new interior design scheme of Society of the Blind Centre for Society of the Blind in Malaysia (Perak branch) at Jalan Medan Ipoh 4, Taman Ipoh Timur, 31400 Ipoh, Perak. Society of The Blind Centre is to attract blind person to experience themselves at this center. This is a new project to propose a center where a blind person can to gather and organized their social activities in a comfort and functional center. Every spaces that proposed would match with the client’s needed and it could be give a comfortable place to disabilities people while come to the center. The site that had been proposed is near to the shopping mall and all time crowded with people. So that, there are many facilities and public transportation is given. This proposal wants to provide a comfortable and sustainable places for disabilities of sight people to study and do their society activities. The concept and images that had been chosen not only suitable with the client but at the same time it would give a positive impact for this project. Besides that, Society of the Blind Center is based on modern and exposed design, goes all the way with the client's needed. Then, disabilities person of sight doesn’t have a place to gather and do their society activities, so that in this center, they can do their activities with comfortable and sustainable place. Some of the data and information are gained through interview, internet, printed media, observation and from the case study either locally and international.